The sociolinguistics of sign languages - Lucas, Ceil (Cambridge University Press, 2001)
This is an accessible introduction to the major areas of sociolinguistics as they relate to sign languages and deaf communities. It brings together a team of leading experts in sign linguistics and covers a wide range of topics including variation, multilingualism, bilingualism, language attitudes and discourse analysis.